Towards Effective Combination of Prior Knowledge and Cognitive Styles in Adaptive Educational Hypermedia Systems - Mampadi, Freddy; Mokotedi, Aubrey Pheto (International Journal of Emerging Technologies in Learning (iJET), 2012)
Adaptive Educational Hypermedia Learning Systems (AEHS) have been developed and evaluated over the past decade. These AEHS tailored navigational support and presentation of content basing on either prior knowledge or cognitive styles of students separately. The empirical evaluations of the AEHS showed that, generally, there is positive improvement in the performance and perceptions of students. There is, however, a need to explore how prior knowledge and cognitive styles could be strategically combined in AEHS in order to maximize learning and comprehension of educational materials. To this end, this paper pursues this exploration by presenting results of a comparative analysis between two AEHS, one tailored to students